School strategies in managing the free nutritional meal program as an effort to improve student discipline and achievement - Noval Dwi Prandika; Desli Natalia Tinambunan; Nur Indah Sari; Linardo Pratama (Institute of Information Technology and Social Science (IITSS), 2024)
The free nutritious meal program is one of the government’s initiatives to enhance educational quality by ensuring students’ nutritional needs are met. This study aims to analyze school strategies in managing the free nutritious meal program as an effort to improve students’ discipline and academic achievement. The research employs a literature review method by examining six scholarly articles related to the implementation and impact of nutritious meal programs in schools. The findings reveal that the active involvement of schools in planning, organizing, and evaluating the program plays a vital role in its success. Properly managed programs have shown positive effects on students’ attendance, discipline, and learning motivation by providing sufficient nutritional support. Therefore, effective management strategies at the school level are crucial to fostering a healthy, productive, and sustainable learning environment.